2021
DOI: 10.3389/fmolb.2021.645470
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant DNA Methylation-Mediated FOXF2 Dysregulation Is a Prognostic Risk Factor for Gastric Cancer

Abstract: Background: The prognosis of gastric cancer (GC) patients is poor. The effect of aberrant DNA methylation on FOXF2 expression and the prognostic role of FOXF2 methylation in GC have not yet been identified.Methods: The RNA-Seq and gene methylation HM450 profile data were used for analyzing FOXF2 expression in GC and its association with methylation level. Bisulfite sequencing PCR (BSP) was performed to measure the methylation level of the FOXF2 promoter region in GC cell lines and normal GES-1 cells. The cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…For example, according to our results, decreased FOXF2 expression has been reported as an independent predictor of poor prognosis for patients with early-stage NSCLC [76]. FOXF2 deregulation ought to an aberrant DNA methylation status has also recently been identified for gastric cancer [77]. In the case of MICA, Okita et al reported that PD-L1 low /MICA/B high is associated with a better clinical outcome in patients with stage I-IIIA NSCLC.…”
Section: Discussionsupporting
confidence: 70%
“…For example, according to our results, decreased FOXF2 expression has been reported as an independent predictor of poor prognosis for patients with early-stage NSCLC [76]. FOXF2 deregulation ought to an aberrant DNA methylation status has also recently been identified for gastric cancer [77]. In the case of MICA, Okita et al reported that PD-L1 low /MICA/B high is associated with a better clinical outcome in patients with stage I-IIIA NSCLC.…”
Section: Discussionsupporting
confidence: 70%
“…More and more corroboration alludes to a crucial role for aberrant DNA methylation in the initiation and development of GC. [25][26][27][28] To begin our investigation, we used Pearson coefficients to see if the JAM3 methylation status affected JAM3 mRNA expression. In GC tissues, a strong inverse connection was seen between JAM3 methylation and JAM3 mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…FOXF2 is mainly expressed in the epithelial–mesenchymal cells of the respiratory tract, digestive tract, urinary tract, and other organs and is involved in extracellular matrix synthesis, mutual transformation between the epithelium and mesenchymal tract, and embryonic and tissue development. 8 10 FOXF2 is correlated with tumor progression, metastasis of breast cancer, 11 , 12 lung cancer, 13 – 15 hepatocellular carcinoma (HCC), 16 , 17 colorectal cancer (CRC), 18 22 prostate cancer (PC), 23 – 25 gastric cancer (GC), 26 , 27 oral cancer, 28 ovarian cancer (OC), 29 mouse rhabdomyosarcoma, 30 bladder cancer, 31 and esophageal squamous cell carcinoma. 32 FOXF2 has shown inhibitory effects in most tumors, such as liver cancer 16 , 17 and prostate cancer, 25 and shown tumor-promoting effects in lung cancer 14 and mouse rhabdomyosarcoma.…”
Section: Introductionmentioning
confidence: 99%